Mesopores Silica and Chitosan Coated Nanoparticles for Targeted Controlled Drug Delivery in Pancreatic Cancer Therapy - Nitin Yadav, Megha Tiwari*, Vishal Dubey, Akanksha Sharma, Jitendra Kumar, Smriti Singh Yadav, Mohd. Abuzar and Shikhar Singh (Journal of Neonatal Surgery, 2025)
Pancreatic cancer is a very aggressive and fatal cancer that is often diagnosed late with limited therapeutic choices. Conventional chemotherapy is faced with considerable limitations such as low drug bioavailability, systemic toxicity, and rapid clearance of drugs, leading to less-than-optimal therapeutic effects. Targeted drug delivery systems have now become a promising field to avoid these limitations. Among the other nanocarriers, chitosan-coated nanoparticles and mesoporous silica nanoparticles (MSN) are prospective carriers for targeted and controlled delivery of anticancer drugs in cancer treatment because of their distinguished physicochemical properties, including high surface area, tunable pore size, and biocompatibility.